HIV and CXCR4 in a kiss of autophagic death - Levine, Beth; Sodora, Donald L. (The Journal of Clinical Investigation, 2006)
AIDS is characterized by CD4+ T lymphocyte depletion, yet the mechanisms underlying this central aspect of HIV pathogenesis are still poorly understood. In this issue of the JCI, Espert et al. identify a mechanism by which the HIV envelope glycoprotein can induce death in uninfected CD4+ T cells (see the related article beginning on page 2161). The HIV envelope glycoprotein interacts with CXC chemokine receptor 4 to activate the lysosomal degradation pathway of autophagy, which is necessary for both apoptotic and nonapoptotic cell death.